Immunological basis of vaccination - Ariyanto Harsono (Paediatrica Indonesiana, 2003)
The basic mechanisms of body defencesagainst infectious diseases are both non-specific and specific immune systems. Non-specific immunity refers to mechanism ofprotection that do not require specific recognition ofantigen, but that increase the protection afforded byspecific immune mechanisms. Non-specific immunemechanisms include phagocytes, acute inflammatoryresponses, type-1 interferon, and tumour necrosingfactor. Specific immunity consists of mechanisms ofprotection that require specific recognition of antigen.This immunity is highly specific, inducible,discriminatory and unforgotten T lymphocyte-dependent response. Normal specific immunityoperates under Major Histocompatibility Complexrestriction. It is the ability of this immune system torefine its antigen recognition domains and establishimmunological memory that underlies the success ofactive vaccination.